A New Social Risk? Social-Scientific Knowledge and Work-Life Balance in Twentieth-Century Finland. Issue 1 (23rd July 2015) - Eräranta, Kirsi
Abstract : Work-life balance, or the reconciliation of work and family, has been discussed recently as a "new social risk" in comparative research on the welfare state. According to this discussion, the social security systems of traditional welfare states were built after World War II in order to protect (male) breadwinners against the "old social risks" such as the loss of income due to old age, sickness, accident, or unemployment. Scholars have argued, however, that these postwar policies have been inadequate for dealing with the new types of risks that resulted from complex changes in employment practices and family life. This article reflects critically upon the conceptualization of work-life balance as a new social risk by focusing on one of the Nordic countries, which have come to be known for their policies that combine (female) parenthood and paid work. In particular, it analyzes the problematization and governance of work-family reconciliation in twentieth-century Finland. Overall, the article argues that social scientific knowledge played a key role in the ways in which work-life balance was rendered intelligible and manageable as a social policy issue.